Pendampingan Perencanaan Strategi dan Manajemen Risiko pada Pengembangan Swipewash Marketplace Layanan Laundry - Arietra, Intan Pertiwi Noor; Negoro, Dimas Angga; Kustiawan, Unggul; Abadi, Ferryal (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
SwipeWash is a technology-based startup focused on laundry marketplace services with a pick-up-delivery model and e-commerce integration. During its development, SwipeWash faced various challenges, including business strategy planning, operational management, and risk management. This mentoring program aims to assist partners in developing a comprehensive business strategy and a measurable, technology-based risk management system. The mentoring method includes identifying partner problems and needs, analyzing the situation, planning strategies and developing recommendations, implementing mentoring, and evaluating and monitoring. The mentoring results indicate that partners gained clearer direction in identifying target markets, improving managerial capacity, and developing risk mitigation measures across operational, financial, technological, and reputational aspects. With the right strategy and sound risk management, SwipeWash has the opportunity to strengthen its position in the digital laundry service market, increase consumer trust, and sustainably expand its service reach.